PENERAPAN MODIFIKASI ALAT UNTUK MENINGKATKAN EFEKTIFITAS PEMBELAJARAN LOMPAT JAUH GAYA JONGKOK - Anang Aliansyah; Athar Athar (Lambung Mangkurat University, 2013)
Modification Application Tool for Improving the Effectiveness of Learning Styles Long Jump Squat. This study aims to determine the extent to which the use of a modified tool in improving learning outcomes long jump fifth grade students of SDN Belandean I Alalak District of Barito Kuala district. The method used in this study is the method of action research (PTK) is in the form of a reflective research. Observations during the learning process takes place and the data analysis is based on observations made by the supervisor. The subjects of this study were fifth grade I Belandean Elementary School District of Alalak. Where the number of learners in classes V to 20 learners. Based on the analysis of data in two cycles, that by applying a modified approach to learning by modifying tool boxes indicate a more effective learning. This situation is expressed by an increase in the average value of each cycle students in the fifth grade students of SDN Belandean I Alalak District of Barito Kuala district. Showed an increase in the value criteria of completeness Minimal (KKM) that is considered more qualified Keywords: Modification learning tool, long jump squat style